INTEGRASI KEPEMIMPINAN INSTRUKSIONAL DAN PENGUATAN PROFESIONALISME GURU PAUD - Miftah Farid; Agita Violy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The improvement of Early Childhood Education (ECE) quality is strongly influenced by the quality of school leadership and teacher professionalism. Instructional leadership is viewed as a leadership approach oriented toward learning processes and the development of teachers’ capacities, while ECE teacher professionalism encompasses pedagogical, personal, social, and professional competencies that are integrally reflected in instructional practice. This article aims to analyze the integration of instructional leadership and the strengthening of ECE teacher professionalism based on a review of recent literature. The method employed is a literature review of scholarly articles, books, and relevant policy documents published within the last ten years. Data analysis was conducted using a thematic approach to identify patterns of relationships, integrative practices, and research gaps. The findings indicate that adaptive, collaborative, and data-driven instructional leadership plays a significant role in enhancing ECE teacher professionalism through continuous academic supervision, internal professional development, and the cultivation of reflective and collaborative school cultures. ECE teacher professionalism is determined not only by technical competencies but also by personal attributes and the ability to build educational relationships with children, parents, and the broader school community. The integration of instructional leadership and teacher professionalism forms a sustainable learning ecosystem oriented toward the holistic development of children. This review provides a conceptual contribution to the improvement of ECE quality and may serve as a foundation for empirical research and policy formulation in early childhood education.